Super-Resolution Reactivity Mapping of Nanostructured Catalyst Particles - Roeffaers, Maarten B.J; De Cremer, Gert; Libeert, Julien; Ameloot, Rob; Dedecker, Peter; Bons, Anton-Jan; Bückins, Matthias; Martens, Johan A; Sels, Bert F; De Vos, Dirk E; Hofkens, Johan (Angewandte Chemie (International ed.), 2009)
Its a small world: Nanoscale reactivity maps of working heterogeneous catalysts are recorded under in situ conditions by localizing single fluorescent reaction products (see picture). This approach allows quantification of the reactivity of catalytic nanodomains.